Proximate composition, lipid, fatty acids and cholesterol content of edible meat cuts From Tegu lizard Tupinambis merianae - Caldironi, Hugo Alfredo (2006)
The proximate composition, fatty acid composition and cholesterol content of three different cuts of meat from tegu Tupinambismerianae were determined. Moisture (72.070.7%), protein (23.670.7%), fat (4.071.3%) and ash (1.270.2%) did not differ from valuesobtained from beef or chicken meat. The cholesterol content (18.275.8 mg/100 g tissue) was similar among the cuts and was lower in tegumeat than in other meats of similar fat content such as beef, chicken or fish. The relation between polyunsaturated and saturated fattyacids (1.09) was comparable to that of some species of fish, and the fat presents nutritional qualities comparable with those of chickenmeat